The PEEI pathway: a learning innovation for smarter learning and better grades - Nordin, Jennifah; Yusuf, Nur Afisha; Chai, Shin Yi; Jugah, Ivy; Sadikin, Sarehan (2025)
Transitioning from school to university education poses substantial challenges for students, particularly those diploma and undergraduate learners. One key difficulty is the lack of critical explanatory skills, specifically the ability to express thought and explain ideas clearly, convincingly, and analytically. This deficiency often contributes to poor individual performance in coursework, poor subject performance, and an overall decline in program achievement. Conversely, the ability to communicate ideas effectively is a strong determinant of academic success. To address this issue, the PEEI approach, a student-centered framework was introduced and implemented. PEEI stands for Point, Elaboration, Example, and Impact. This four-step method is designed to guide students in organizing and expressing their thoughts more effectively. This approach serves as a practical tool for guiding students to identify their key point, elaborate on it, support it with relevant examples, and discuss its implications. Students are guided to apply the PEEI framework during tutorial sessions. Feedback indicates that most students find the PEEI approach beneficial in refining their ability to present ideas more effectively. Moreover, lecturers can utilize this approach to improve course outcomes and use it as effective teaching strategies in higher education. PEEI proves to be a simple yet powerful method for enhancing students’ articulation skills in higher education learning environments.